2015
DOI: 10.3892/mmr.2015.4499
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of fermented extract of Ophiopogon japonicas on thrombin-induced vascular smooth muscle cells

Abstract: Ophiopogon japonicus is known to have various pharmacological effects. The present study investigated the effects of an extract of fermented Ophiopogon japonicas (FEOJ) on thrombin‑treated vascular smooth muscle cells (VSMCs). FEOJ treatment inhibited the proliferation of VSMCs treated with thrombin as indicated by an MTT assay. These inhibitory effects were associated with decreased phosphorylation of AKT, reduced expression of cyclin D1 and increased expression of p27KIP1 in thrombin‑induced VSMCs. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The first study reported that brazilin, a homoisoflavonoid, inhibited PDGF-induced proliferation of rat aortic VSMCs and induced cell-cycle arrest at G 0 /G 1 phase [69]. The other study showed that the homoisoflavonoid-rich plant, Ophiopogon japonicas , exhibited anti-proliferative effects on thrombin-induced rat aortic VSMCs [70]. Similar to brazilin and Ophiopogon japonicas , MP induced the upregulation of p27 [69,70].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first study reported that brazilin, a homoisoflavonoid, inhibited PDGF-induced proliferation of rat aortic VSMCs and induced cell-cycle arrest at G 0 /G 1 phase [69]. The other study showed that the homoisoflavonoid-rich plant, Ophiopogon japonicas , exhibited anti-proliferative effects on thrombin-induced rat aortic VSMCs [70]. Similar to brazilin and Ophiopogon japonicas , MP induced the upregulation of p27 [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…The other study showed that the homoisoflavonoid-rich plant, Ophiopogon japonicas , exhibited anti-proliferative effects on thrombin-induced rat aortic VSMCs [70]. Similar to brazilin and Ophiopogon japonicas , MP induced the upregulation of p27 [69,70]. This suggests that homoisoflavonoids attenuate VSMC proliferation by targeting cell cycle regulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts obtained by fermentation of Rhus verniciflua bark exhibited anticancer activity against the colon cancer cell line HCT-116 and showed the ability to induce apoptosis and inhibit the hedgehog pathway [24]. Dual fermentation of Ophiopogon japonicas extract against Cordyceps militaris, Bifidobacterium longum, Lactobacillus plantarum, and Enterococcus faecium yielded a fermented extract that can prevent cardiovascular disease associated with vascular smooth muscle cell (VSMC) proliferation and migration [25]. Moreover, the fermented plant extract obtained from ginseng in the presence of Aspergillus usamii showed higher anticancer activity against human hepatoma cells (HepG2) and the human colon cancer cell line (DLD-1) compared to the unfermented ginseng extract [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…Fermented Rhus verniciflua stem bark extracts showed anticancer activity in a colon cancer cell line HCT-116 and the ability to induce senescence or apoptosis and inhibit the hedgehog pathway [ 11 ]. The fermented Ophiopogon japonicas extract with Cordyceps militaris (first fermentation for 10 days), Lactobacillus plantarum, Enterococcus faecium , and Bifidobacterium longum (second fermentation for 2 days) can prevent cardiovascular diseases associated with the proliferation and migration of vascular smooth muscle cells (VSMCs) [ 12 ]. In turn, fermented Withania somnifera, Emblica officinalis , and Bacopa monnieri extract with Beauveria bassiana ATCC 7159 reduced chick embryo chorioallantoic membrane (CAM) vascularization, suggesting its anti-angiogenic potency [ 13 ].…”
Section: Introductionmentioning
confidence: 99%